Practical Internet of Things with JavaScript : build standalone exciting IoT projects with Raspberry Pi 3 and JavaScript (ES5/ES6) /: build standalone exciting IoT projects with Raspberry Pi 3 and JavaScript (ES5/ES6). (2017) - Ravulavaru, Arvind
No abstract available